Trends in clinical outcomes of older hemodialysis patients: data from the 2023 Korean Renal Data System (KORDS) - Hyunglae Kim; Seon A Jeong; Kyeong Min Kim; Sun Deuk Hwang; Sun Ryoung Choi; Hajeong Lee; Ji Hyun Kim; Su Hyun Kim; Tae Hee Kim; Ho-Seok Koo; Chang-Yun Yoon; Kiwon Kim; et al. (The Korean Society of Nephrology, 2024)
With an increasing aging population, the mean age of patients with end-stage kidney disease (ESKD) is globally increasing. However, the current clinical status of elderly patients undergoing hemodialysis (HD) is rarely reported in Korea. The current study analyzed the clinical features and trends of older patients undergoing HD from the Korean Renal Data System (KORDS) database. The patients were divided into three groups according to age: <65 years (the young group), n = 50,591 (35.9%); 65-74 years (the younger-old group), n = 37,525 (26.6%); and ≥75 years (the older-old group), n = 52,856 (37.5%). The proportion of older-old group undergoing HD significantly increased in incidence and decreased in prevalence from 2013 to 2022. The median levels of hemoglobin, serum creatinine, albumin, calcium, phosphorus, and intact parathyroid hormone significantly decreased in the older-old group. The proportions of arteriovenous fistula creation and left forearm placement showed decreased trends with age. Although the utilization of low surface area dialyzers increased with age, the dialysis adequacy, including urea reduction ratio and Kt/V was within acceptable range in the older-old group on HD. Over the past 20 years, the mortality rate in the older-old group has increased, with cardiovascular diseases decreasing and infectious diseases increasing. The incidence of elderly patients undergoing HD has increased over time, but the high mortality of the older-old group needs to be solved. Therefore, it is imperative to develop holistic strategies based on age and individual needs for patients with ESKD.